2004
DOI: 10.2134/agronj2004.1572
|View full text |Cite
|
Sign up to set email alerts
|

Economic Feasibility of Variable‐Rate Nitrogen Application Utilizing Site‐Specific Management Zones

Abstract: Variable-rate technology (VRT) has been developed to variablyThe potential for improved profitability due to variapply crop inputs to manage in-field variability. Although growers have able-rate N application depends on identifying areas in begun to adopt VRT, its profitability is uncertain in N management. the field where additional N inputs will increase revenue The objective of this study was to assess the economics of uniform vs. variable-rate N fertilizer application under two N application scenarios on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
4
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(127 citation statements)
references
References 10 publications
3
117
4
3
Order By: Relevance
“…Another major factor contributing to low NUE in current strategies has been uniform application rates of fertilizer N to spatially variable landscapes, even though numerous field studies have indicated economic and environmental justification for spatially variable N applications in many agricultural landscapes (Mamo et al, 2003;Hurley et al, 2004;Koch et al, 2004;Scharf et al, 2005;Shahandeh et al, 2005;Lambert et al, 2006;Hong et al, 2007). Uniform applications within fields discount the fact that N supplies from the soil, crop N uptake, and response to N are not the same spatially (Inman et al, 2005).…”
Section: Causes Of Low Nue For Current N Management Strategiesmentioning
confidence: 99%
“…Another major factor contributing to low NUE in current strategies has been uniform application rates of fertilizer N to spatially variable landscapes, even though numerous field studies have indicated economic and environmental justification for spatially variable N applications in many agricultural landscapes (Mamo et al, 2003;Hurley et al, 2004;Koch et al, 2004;Scharf et al, 2005;Shahandeh et al, 2005;Lambert et al, 2006;Hong et al, 2007). Uniform applications within fields discount the fact that N supplies from the soil, crop N uptake, and response to N are not the same spatially (Inman et al, 2005).…”
Section: Causes Of Low Nue For Current N Management Strategiesmentioning
confidence: 99%
“…Ils se limitent au gain que représentait la diminution des quantités d'intrant ou aux marges brutes. De plus, ces expérimentations ont porté sur des cultures spécifiques, blé le plus souvent, (Duval et al, 2007), ou maïs (Koch et al, 2004) et/ou un type d'intrant tel que l'azote en général (Dailey et al, 2006 ;De Vuyst et Halvorson, op. cit.…”
Section: Un Contexte Politique Volontaristeunclassified
“…Although precise application of N is attainable through variable-rate technology, a great challenge facing its widespread utilization is the lack of a robust and fast measurement system for real-time monitoring of NO 3 dynamics in soil water (Zhang et al, 2002). In situ monitoring of NO 3 -N concentrations can help to optimize the application of N-rich fertilizers, reduce the risk of NO 3 -N leaching to water bodies, and evaluate the effi ciency of best management practices targeted on the improvement of N uptake by plants during the growing season (Roberts et al, 2002(Roberts et al, , 2010Koch et al, 2004). Traditional methods for measuring soil NO 3 concentration are accurate, but at the same time they are labor intensive, time consuming, expensive, and destructive, which limits their application in real-time in situ monitoring for large areas.…”
Section: Estimating Soil Solution Nitrate Concentration From Dielectrmentioning
confidence: 99%